1989
DOI: 10.1002/ppul.1950070305
|View full text |Cite
|
Sign up to set email alerts
|

Variation in peak expiratory flow of normal and asymptomatic asthmatic children

Abstract: Peak expiratory flow (PEF) variation was measured in 18 healthy children (Group I) aged 9.25 to 13.3 years (mean, 11 years) and in 17 asymptomatic asthmatic children (Group II) aged 8.75 to 14.25 years (mean, 11.9 years) receiving no bronchodilators. PEF was measured four times a day for a period of 10-14 days. There were no differences between Group I and Group II regarding age, height, weight, sex, duration of the study, and overall mean PEF values. Mean daily PEF variation amplitude (difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
(2 reference statements)
0
6
1
Order By: Relevance
“…Most studies have reported greater diurnal variation in PEF both in adults and children with asthma using the (HI-LO)VRB index [12,19,[28][29][30]. However, HENDERSON and CARSWELL [31] found mean values of 8.8% in normal children and 12.5% in asthmatics -a smaller difference than in adults and similar to the low PEF variation in the present study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Most studies have reported greater diurnal variation in PEF both in adults and children with asthma using the (HI-LO)VRB index [12,19,[28][29][30]. However, HENDERSON and CARSWELL [31] found mean values of 8.8% in normal children and 12.5% in asthmatics -a smaller difference than in adults and similar to the low PEF variation in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…All values for lung function were normalized by expressing them as percentage of predicted normal for each patient using the appropriate European Coal and Steel Community (ECCS) normal data. The diurnal variation in PEF on a day-today basis, the (HI-LO) VRB index, was calculated as described by ALBERTINI et al [12] and recommended in the international consensus report on the diagnosis and treatment of asthma [4], where:…”
Section: Analysis Of Datamentioning
confidence: 99%
“…Albertini and coworkers found corresponding values of 15 2% in well controlled asthmatic children and 9 9% in non-asthmatic children. 23 Brand and co-workers24 and Henneberger and coworkers25 studied asthmatic subjects only and found mean values of 14 5% and 17% respectively for amplitude % mean of PEF values. We also examined the circadian variations using cosinor analysis which matches biological rhythms with sinusoidal functions.…”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, a variety of indoor and outdoor pollutants, including bioaerosols, have been shown to affect lung function in those with pre-existing disease [8, 10, 11, 16, 23, 83-86, 89, 111, 159, 160, 162-164, 166, 173-176] as well as symptoms; PEF appears to be a more sensitive instrument for detecting such changes [166,177,178].…”
Section: Pm/o 3 and Copdmentioning
confidence: 99%